Large single-crystal growth and characterization of the narrow-gap semiconductor TlBiS2 - Özer, Mehmet; Paraskevopoulos, K. M.; Anagnostopoulos, A. N.; Kokou, S.; Polychroniadis, E. K. (My University, 1996)
TIBiS2 is a narrow-gap semiconductor with a layered structure, isoelectronically analogous to PbS. Large single crystals were grown by the Bridgman - Stockbarger method from the melt and characterized by x-ray diffraction. The lattice parameters were determined and the discrepancy between those already reported was removed. From IR reflectivity measurements in the plasma region, the number of carriers was calculated. Also a strong anisotropy of the electrical conductivity was detected and the narrow-gap character of the material was supported by electrical measurements in the range of 10 - 300 K.